Hukum dan undang-undang perkebunan / Teguh Prasetyo, Kadarwati Budihardjo, Purwadi ; editor, Arie Purnomosidi - TEGUH PRASETYO; Kadarwati Budihardjo; Purwadi; Arie Purnomosidi (Nusa Media, 2013)
xii, 219 hlm. ; 21 cm